Francisella tularensis subsp. holarctica wild-type is able to colonize natural aquatic ex vivo biofilms - Schaudinn, Christoph; Rydzewski, Kerstin; Meister, Beate; Grunow, Roland; Heuner, Klaus (Frontiers in Microbiology, 2023)
Biofilms are a matrix-associated lifestyle of microbial communities, often enabling survivability and persistence of such bacteria. The objective of this study was to investigate the survival of the wild-type strain A-271 of Francisella tularensis subsp. holarctica (Fth) in a natural aquatic ex vivo biofilm. To that purpose, we allowed Fth-A-271 to produce its own biofilm on solid surfaces but also to colonize naturally formed biofilms from aquatic habitats, which were infected with Francisella in the laboratory. The survival rates of the bacteria in biofilms were compared to those of planktonic bacteria as a function of the employed culture condition. It could be shown by light- and electron microscopy that Fth is able to form a complex, matrix-associated biofilm. The biofilm form of Francisella showed longer cultivability on agar plates in natural water when compared to planktonic (free-living) bacteria. Be it as a part of the existing ex vivo biofilm or free-floating above as planktonic bacteria, more than 80% of Francisella were not only able to survive under these conditions for 28 days, but even managed to establish microcolonies and areas with their own exclusive biofilm architecture within the ex vivo biofilm. Here, we can demonstrate for the first time that a Francisella tularensis wild-type strain (Type B) is able to successfully colonize an aquatic multi-species ex vivo biofilm. It is worthwhile to speculate that Fth might become more persistent in the environment when it forms its own biofilm or integrates in an existing one. Multi-species biofilms have been shown to be more resistant against stress compared to single-species biofilms. This may have an important impact on the long-term survival of Francisella in aquatic habitats and infection cycles in nature.